Association of genetic polymorphism with the mutation status of the BRCA1/2 genes in spontanous breast cancer - Polinyk, S.I.; Rybchenko, L.A.; Klymenko, S.V.; Zaharceva, L.M.; Klimuk, B.T. (Вiopolymers and Cell, 2017)
Aim. To study ssociation of the FGFR2 and TOX3/LOC643714 genetic polymorphisms with the BRCA1/2 mutation status in Ukrainian female breast cancer patients without ionizing radiation impact in their histories. Methods. Molecular genetics methods were used. Non-parametric data were evaluated using the two-way Fisher’s Exact test. Statistical analysis was performed using the StatPlus Pro program package. Results. Association of genetic polymorphisms rs2981582 of the FGFR2 gene and rs3803662 of the TOX3/LOC643714 gene with the mutation status of the BRCA1/2 genes in breast cancer patients non-treated with ionizing radiation in their histories was shown. Conclusion. The association between the minor genotype of the TOX3/LOC643714 gene and the positive status of the BRCA1 gene was found to be reliable. No statistic association was found between homozygotes for the major alleles and heterozygote polymorphisms of the FGFR2, TOX3 / LOC643714 genes, with or without BRCA1/2 mutations (p < 0.05). Мета. Визначення асоціації носійства генетичних поліморфізмів генів FGFR2, TOX3/LOC643714 з мутаційним статусом генів BRCA1/2 у жінок України хворих на рак молочної залози, які не мають впливу іонізуючого випромінювання в анамнезі. Методи. Молекулярно-генетичні методи дослідження. Непараметричні дані оцінювали з використанням точного тесту Фішера в двобічному варіанті. Статистичний аналіз проводили з використанням пакету програми StatPlus Pro. Результати. Показано,що існують асоціації носійства генетичних поліморфізмів rs2981582 гена FGFR2, rs3803662 гена TOX3/LOC643714 з мутаційним статусом генів BRCA1/2 жінок хворих на РМЗ без іонізуючого випромінювання в анамнезі. Висновки. Серед досліджених генетичних поліморфізмів достовірним виявили асоціацію між мінорним генотипом ТТгена TOX3/LOC643714 та позитивним статусом гена BRCA1. Не знайдено статистичної асоціації серед гомозигот за мажорними алелями та гетерозигот поліморфізмів генів FGFR2, TOX3/LOC643714, з наявністю або відсутністю мутацій BRCA1/2 (p < 0,05). Цель. Проанализировать ассоциацию носительства генетических полиморфизмов генов FGFR2, TOX3 / LOC643714 с мутационным статусом генов BRCA1 / 2 у женщин Украины, больных раком молочной железы, не имеющих влияния ионизирующего излучения в анамнезе. Методы. Молекулярно-генетические методы исследования. Непараметрические данные оценивались с использованием точного теста Фишера в двустороннем варианте. Статистический анализ был проведен с использованием пакета программы StatPlus Pro. Результаты. Определена ассоциация носительства генетических полиморфизмов rs2981582 гена FGFR2, rs3803662 гена TOX3 / LOC643714 с мутационным статусом генов BRCA1/2 женщин, больных РМЖ, без ионизирующего излучения в анамнезе. Выводы. Среди исследованных генетических полиморфизмов была обнаружена ассоциация между минорным генотипом ТТ гена TOX3 / LOC643714 и положительным статусом гена BRCA1. Не найдено статистической ассоциации среди гомозигот по мажорным аллелям и гетерозигот полиморфизмов генов FGFR2, TOX3 / LOC643714, с наличием или отсутствием мутаций BRCA1/2 (p < 0,05).